Environmental economics: An introduction - Field, Barry C. (McGraw-Hill, 2002)
Barry Field's Environmental Economics, 3e, examines all the facets of the connection between environmental quality and the economic behavior of individuals and groups of people. The book contains 21 chapters covering Cost and Benefits of Environmental Policy, Environmental Analysis, Policy Analysis, US Policy (Air Pollution, Toxic Wastes, State and Local Issues), and International Environmental Issues. Barry Field's other text with McGraw-Hill/Irwin, Natural Resource Economics (©2001), may be packaged with Environmental Economics, 3e, at a discount.